2019
DOI: 10.3390/app9122518
|View full text |Cite
|
Sign up to set email alerts
|

A Convolutional Neural Network Based Auto Features Extraction Method for Tea Classification with Electronic Tongue

Abstract: Feature extraction is a key part of the electronic tongue system. Almost all of the existing features extraction methods are "hand-crafted", which are difficult in features selection and poor in stability. The lack of automatic, efficient and accurate features extraction methods has limited the application and development of electronic tongue systems. In this work, a convolutional neural network-based auto features extraction strategy (CNN-AFE) in an electronic tongue (e-tongue) system for tea classification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Yuan et al proposed an automatic feature extraction strategy based on a convolutional neural network in an electronic tongue system for tea classification [ 96 ]. Since each sensor provides a large number of current responses for the analyte, it is challenging to extract effective features from the large number of responses that affect the accuracy of pattern recognition.…”
Section: Chemometric Tools In Biosensingmentioning
confidence: 99%
“…Yuan et al proposed an automatic feature extraction strategy based on a convolutional neural network in an electronic tongue system for tea classification [ 96 ]. Since each sensor provides a large number of current responses for the analyte, it is challenging to extract effective features from the large number of responses that affect the accuracy of pattern recognition.…”
Section: Chemometric Tools In Biosensingmentioning
confidence: 99%
“…So, the method advances the norm using the fusion technique. Authors in 83 suggested the use of the CNN-based auto features extraction (CNN-AFE) method to enhance classification functions. Features extracted using CNN were further classified using a shallow CNN architecture.…”
Section: Related Workmentioning
confidence: 99%
“…They have reported promising results, but they are yet to be deployed in real tea-processing environments. Additionally, CNNs have been adopted to detect diseases and pest-infected leaves (Zhou et al, 2021;Chen et al, 2019;Hu et al, 2019;Karmokar et al, 2015).…”
Section: Related Workmentioning
confidence: 99%